2013
DOI: 10.3109/14767058.2013.847417
|View full text |Cite
|
Sign up to set email alerts
|

Effect of povidone iodine on thyroid functions and urine iodine levels in caesarean operations

Abstract: The absorption of PI by the skin was found to lead to changes in fT3, TSH, and urine iodine excretion values in the mothers. The findings of this study of Caesarean operations, which have a short duration, might be a signal to be careful of thyroid hormone effects in operations lasting longer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 11 publications
1
12
0
1
Order By: Relevance
“…15 The effects of povidone iodine used during caesarean operations on maternal thyroid hormones was analysed and it was determined that when povidone iodine was used, preoperative and postoperative, thyroid hormone changes occurred. 16 Povidone iodine produced a significant increase in postoperative TSH values compared with preoperative values and it influenced TSH values in the mother but due to the short duration of caesarean operations povidone-iodine use may be reliable. 16 However, in operations lasting longer hours, if thyroid hormone level changes occur, the use of povidone-iodine should be considered.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…15 The effects of povidone iodine used during caesarean operations on maternal thyroid hormones was analysed and it was determined that when povidone iodine was used, preoperative and postoperative, thyroid hormone changes occurred. 16 Povidone iodine produced a significant increase in postoperative TSH values compared with preoperative values and it influenced TSH values in the mother but due to the short duration of caesarean operations povidone-iodine use may be reliable. 16 However, in operations lasting longer hours, if thyroid hormone level changes occur, the use of povidone-iodine should be considered.…”
Section: Discussionmentioning
confidence: 96%
“…16 Povidone iodine produced a significant increase in postoperative TSH values compared with preoperative values and it influenced TSH values in the mother but due to the short duration of caesarean operations povidone-iodine use may be reliable. 16 However, in operations lasting longer hours, if thyroid hormone level changes occur, the use of povidone-iodine should be considered.…”
Section: Discussionmentioning
confidence: 96%
“…Cord blood hyperthyrotropinaemia has been reported after disinfection of the skin with PVP-I during the last trimester of pregnancy, labour and also during caesarean section in mild to moderate iodine-deficient European countries3 8 and Turkey 9. However, Tahirović et al ,10 Brown et al 11 and Ordookhani et al 4 reported that, in iodine-replete regions, routine disinfection of the skin with PVP-I did not increase the incidence of cord blood hyperthyrotropinaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previously used povidone-iodine solutions for skin cleansing, resulting in the transcutaneous iodine absorption, were replaced by chlorhexidine-based antiseptics [87]. Findik et al indicated that the use of povidone iodine solutions during the caesarean sections influenced free triiodothyronine (fT3) thyroid-stimulating hormone (TSH) values in the mother, although it has not statistically significantly influenced urine iodine levels [90]. Additionally, it was also reported that use of iodine-containing antiseptics increased the urinary iodine status, without influencing the TSH status in the neonate [91].…”
Section: Parenteral Nutritionmentioning
confidence: 99%